The Use of Growl Vocal Technique to Enhance Voice Quality in Singing Pop Songs - Suryati, Suryati (Institut Seni Indonesia Yogyakarta, 2023)
This study aims to provide solutions for students of Music Education Study Program of Indonesia Institute of the Arts Yogyakarta who face problems in singing pop songs, particularly to reach high notes. Growl is a kind of vocal technique for producing growling sounds. Initially, Growl vocal technique was used by metal or rock vocalists. However, this technique can be applied to pop songs as a variation. As a result, it can be functioned as a solution to reach high notes for the singers having low range of notes. This study focused on the process of practicing Growl vocal technique and the use of Growl when singing pop songs. The author implemented qualitative method emphasizing on cas study approach. The data collection was carried out through literature studies, observations, and interviews by selecting sample from the respondents engaging in this study case in which the subjects of the study were Pop Jazz vocal students in Music Education Study Program of Indonesia Institute of the Arts Yogyakarta. The application of Growl Vocal Technique is highly efficacious when singing both low and high notes in legato manner. In addition, Growl can be an emphasis on the specific lines of song lyrics to convey the enotional meaning of that part. Furthermore, it also can be functioned as an alteration to create divergence of a singer in using vocal techniques when singing. It leads to a novelty that the use of Growl vocal technique can be said to be an aesthetic expression to make voice much more amusing.